2015
DOI: 10.1590/s1984-29612015012
|View full text |Cite
|
Sign up to set email alerts
|

Parasites in the mangrove oyster Crassostrea rhizophorae cultivated in the estuary of the Graciosa River in Taperoá, Bahia

Abstract: Parasites in the mangrove oyster Crassostrea rhizophorae cultivated in the estuary of the Graciosa River in Taperoá, BahiaParasitos na ostra-do-mangue Crassostrea rhizophorae cultivada no estuário do rio Graciosa em Taperoá, Bahia AbstractIn this work, parasites associated with the mangrove oyster Crassostrea rhizophorae were studied at a cultivation unit in the estuary of the Graciosa River in Taperoá, Bahia. On a monthly basis, between April 2011 and March 2012, 20 oysters were collected, measured and fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…The data from these studies do not allow comparative ultrastructural descriptions in relation to species that had previously been described (AZEVEDO & MATOS, 1999;AZEVEDO & PADOVAN, 2004;MAGALHÃES et al, 2006). These descriptions of undetermined Nematopsis species (BRITO et al, 2010;COVA et al, 2015;LUZ & BOEHS, 2015;PINTO & BOEHS, 2008;SABRY & MAGALHÃES, 2005) seem to correspond to the morphological characteristics of oocysts of the genus Nematopsis infecting Brazilian fauna that had previously been described.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The data from these studies do not allow comparative ultrastructural descriptions in relation to species that had previously been described (AZEVEDO & MATOS, 1999;AZEVEDO & PADOVAN, 2004;MAGALHÃES et al, 2006). These descriptions of undetermined Nematopsis species (BRITO et al, 2010;COVA et al, 2015;LUZ & BOEHS, 2015;PINTO & BOEHS, 2008;SABRY & MAGALHÃES, 2005) seem to correspond to the morphological characteristics of oocysts of the genus Nematopsis infecting Brazilian fauna that had previously been described.…”
Section: Discussionsupporting
confidence: 65%
“…Considering that some undetermined species of Nematopsis occurring in several hosts belonging to different species (ABDEL-BAKI et al 2012;AZEVEDO & CACHOLA, 1992;BOEHS et al, 2010;BRANDÃO et al, 2013;BRITO et al, 2010;CANESTRI-TROTTI et al, 2000;COVA et al, 2015;KUA et al, 2013;PINTO & BOEHS, 2008;QUEIROGA et al, 2015;SABRY & MAGALHÃES, 2005;SUJA et al, 2016;TUNTIWARANURUK et al, 2004TUNTIWARANURUK et al, , 2015, it is acceptable to think that many of the species thus described may correspond to previously described species. On the other hand, several Nematopsis species have been described from the gregarine stage of the schizogonic phase (CHAMBOUVET et al, 2016;CHAKRABORTI & BANDYOPADHYAY, 2010;JIMÉNEZ et al, 2002;PRASADAN & JANARDANAN, 1996, 2001SHANAVAS et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are extracellular, and live as commensals in the lumen of the digestive gland tubules and acini, such as Stegotricha enterikos Meyer, 1993 (Bower andMeyer, 1993) or Ancicostroma sp. (Cova et al, 2015), or in association with or attached to the gills, such as Trichodina spp. (Xu et al, 2000).…”
mentioning
confidence: 99%
“…Despite of the infection by Nematopsis sp. being associated to a focal hemocytic reaction without significant effects to the bivalve health, as verified in studies in the state of Bahia (COVA et al, 2015), Paraíba (QUEIROGA et al, 2015), and Sergipe (SILVA et al, 2015. Azevedo and Cachola (1992) showed that high levels of infection by Nematopsis sp.…”
Section: Discussionmentioning
confidence: 76%